A Seven-Year Retrospective Study on the Surveillance of Hepatitis B in Laos - Phimpha Paboriboune; Thomas Vial; François Chassagne; Philavanh Sitbounlang; Sengaloun Soundala; Stéphane Bertani; Davone Sengmanothong; Francois-Xavier Babin; Nicolas Steenkeste; Paul Dény; Pascal Pineau; Eric Deharo (International Journal of Hepatology)
Objective. Lao PDR is one of the most highly endemic countries for hepatitis B in Asia and the second country for liver cancer incidence. Therefore, the follow-up of infected individuals through predictive serological markers is of utmost importance to monitor the progression of the pathology and take the decision on treatment. Methods. A retrospective-descriptive cohort study was conducted on 3,857 HBV-infected patients. Information about infection status (viral load, VL), liver function (aminotransferases), and treatments was recorded. Results. M/F sex ratio was 1.77 for a median age of 37. Patients under 37 displayed higher VL than older ones and men had higher VL than women. Initial VL ranged from <50 IU/mL to 2.5 1013 IU/mL. Median aminotransferase values were 45.5 U/L for ALAT and 44 U/L for ASAT, ranging from <8 to >2,000 U/L. Men had higher aminotransferase than women. Globally 20% of patients received treatment (mainly immunostimulant and reverse-transcriptase inhibitors); 11% had high levels of VL and liver enzymes, but only 2% of them were treated. Conclusion. Public health decisions should be taken urgently to rationalise vaccination and provide fair access to early diagnosis and treatment; otherwise the burden of HBV-associated diseases will be overwhelming for Laos in the near future.